Does membership in international organizations increase governments' credibility? Testing the effects of delegating powers - Axel Dreher; Stefan Voigt (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper analyzes whether nation-state governments can increase their credibility by becoming members of international organizations. Credibility is an important asset because it determines the real interest rate and is expected to have an important impact on investment and growth. It is hypothesized that the degree of delegation to international organizations can improve the credibility of nation-state governments. This hypothesis is tested by introducing three new indicators for international delegation. On the basis of panel data for up to 136 countries and the time period from 1984 to 2004, membership in international organizations is significantly and robustly linked with better credibility, here proxied for by country risk ratings. Two more results stand out: the longer a country has had a high level of membership, the higher its credibility, ceteris paribus; and: the credibility-enhancing effect is strongest in countries whose domestic institutions are weak.
Keywords: F02; F21; H11; K33; P26; 330; Delegation of Competence; Credibility; Dilemma of the Strong State; International Organizations; Nationalstaat; Regierung; Mitgliedschaft; Internationale Organisation; Glaubwürdigkeit; Länderrisiko; Welt